Generation of an adenovirus-parvovirus chimera with enhanced oncolytic potential - El-Andaloussi, Nazim; Bonifati, Serena; Kaufmann, Johanna K.; Nettelbeck, Dirk M.; Marchini, Antonio (Journal of virology, 2012)
In this study, our goal was to generate a chimeric adenovirus-parvovirus (Ad-PV) vector that combines the high-titer and efficient gene transfer of adenovirus with the anticancer potential of rodent parvovirus. To this end, the entire oncolytic PV genome was inserted into a replication-defective E1- and E3-deleted Ad5 vector genome. As we found that parvoviral NS expression inhibited Ad-PV chimera production, we engineered the parvoviral P4 early promoter, which governs NS expression, by inserting into its sequence tetracycline operator elements. As a result of these modifications, P4-driven expression was blocked in the packaging T-REx-293 cells, which constitutively express the tetracycline repressor, allowing high-yield chimera production. The chimera effectively delivered the PV genome into cancer cells, from which fully infectious replication-competent parvovirus particles were generated. Remarkably, the Ad-PV chimera exerted stronger cytotoxic activities against various cancer cell lines, compared with the PV and Ad parental viruses, while being still innocuous to a panel of tested healthy primary human cells. This Ad-PV chimera represents a novel versatile anticancer agent which can be subjected to further genetic manipulations in order to reinforce its enhanced oncolytic capacity through arming with transgenes or retargeting into tumor cells.
Published ahead of print 11 July 2012
Gesehen am 27.06.2019